2000
DOI: 10.1097/00003246-200009000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid onset of intestinal epithelial and lymphocyte apoptotic cell death in patients with trauma and shock

Abstract: Focal apoptosis of intestinal epithelial and lymphoid tissues occurs extremely rapidly after injury. Apoptotic loss of intestinal epithelial cells may compromise bowel wall integrity and be a mechanism for bacterial or endotoxin translocation into the systemic circulation. Apoptosis of lymphocytes may impair immunologic defenses and predispose to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(121 citation statements)
references
References 30 publications
5
111
2
3
Order By: Relevance
“…This effect of adoptive transfer of apoptotic cells to decrease sepsis survival is particularly striking considering that mice that had adoptive transfer of necrotic cells had a significant improvement in survival compared with salinetreated mice. Apoptosis is a major cause of death in lymphocytes and gastrointestinal epithelial cells in patients with sepsis and trauma (14,(32)(33)(34). Immunohistochemical studies of spleens from patients dying of sepsis demonstrated focal regions in which 25-50% of cells were positive for markers of apoptosis (14,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect of adoptive transfer of apoptotic cells to decrease sepsis survival is particularly striking considering that mice that had adoptive transfer of necrotic cells had a significant improvement in survival compared with salinetreated mice. Apoptosis is a major cause of death in lymphocytes and gastrointestinal epithelial cells in patients with sepsis and trauma (14,(32)(33)(34). Immunohistochemical studies of spleens from patients dying of sepsis demonstrated focal regions in which 25-50% of cells were positive for markers of apoptosis (14,34).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a major cause of death in lymphocytes and gastrointestinal epithelial cells in patients with sepsis and trauma (14,(32)(33)(34). Immunohistochemical studies of spleens from patients dying of sepsis demonstrated focal regions in which 25-50% of cells were positive for markers of apoptosis (14,34). A recent study of circulating white blood cells from patients with sepsis showed that 15-20% of circulating T and B cells were undergoing apoptosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis causes the marked deletion of immune cells, including natural killer (NK) cells, CD4 + and CD8 + T cells, B cells, and dendritic cells (DC), in various organs of patients dying of sepsis, leading to immunosuppression (Figure 2). Apoptosis of immune cells occurs in lymphoid tissues and gut‐associated lymphoid tissues 15. The loss of intestinal intraepithelial and lamina propria lymphocytes might facilitate bacterial translocation into the systemic circulation, thereby perpetuating the systemic inflammatory response and predisposing to secondary infections.…”
Section: Mechanism Of Sepsis‐induced Immunosuppressionmentioning
confidence: 99%
“…Previous studies have also indicated that stress could damage the function of intestinal mucosal barrier (Hotchkiss et al, 2000;Grogan et al, 2004). The gastrointestinal tract bears the stressful events such as the severe brain injury, trauma, burn, infection, and hemorrhagic shock.…”
mentioning
confidence: 99%